Social wasps (Vespidae: Polistinae) harvesting food bodies of Cecropia Loefl. (Urticaceae) in Central Amazon - Aguiar, Daniel P. P.; Somavilla, Alexandre; Fernandes, Itanna O.; Demarchi, Layon O. (Entomological Communications, 2024)
Social wasps are among the most curious non-ant insects known to harvest food bodies of Cecropia Loefl. The aim of this note is to describe for the first time: (1) interactions between wasp species which harvest food bodies; (2) interactions of these wasps with other insects associated to Cecropia (ants, assassin bugs); (3) the use of a food resource different from müllerian bodies; and (4) wasp species whose association with Cecropia was unknown until now. All records were made in Manaus region and in Uatumã Sustainable Development Reserve (Amazonas State, Brazil), with the aid of a digital camera. The wasp and ant species involved were captured for later identification. The recorded wasp species were: Charterginus xanthura Saussure, 1854, Protopolybia chartergoides Gribodo, 1891, Protopolybia minutissima Spinola, 1851, and Synoeca virginea Fabricius, 1804 (Hymenoptera: Vespidae). The findings corroborate the importance of food bodies not only for Azteca Forel, 1878 ants, but also for other social insects.